Design of biodegradable Zn-Ag-xAl alloys: Investigation of microstructure, corrosion, and bacterial sensitivity for urological implants - Basit, S.; Kartal, F. K.; Ilgazi, M. E.; Arisan, E. D.; Yilmazer, Y.; Dikici, B.; Bulutsuz, A. G.; Dalbayrak, B.; Islamgaliev, R. K.; Yilmazer, H. (ELSEVIER SCIENCE SA, 2025)
In this study, micro-alloyed Zn with Ag and Al was cast and homogenized. The novel ternary Zn alloys were fabricated by the casting method under a controlled atmosphere. Following the fabrication process, the bar-shaped samples underwent homogenization heat treatment at a temperature of 350 degrees C for a duration of 16 h. In the alloy design, the silver (Ag) content was maintained at a constant level of 0.5 wt%, while the influence of aluminum (Al) concentration (x = 0, 0.2, 0.4, 0.6, 0.8 wt%) on the microstructure, hardness, in vitro corrosion behavior, biodegradability, and bacterial susceptibility was systematically examined. The microstructure of the alloys was characterized through detailed analysis using optical microscopy (OM), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Additionally, phase identification of the samples was performed using X-ray diffraction (XRD). The degradation behavior of the alloys was systematically evaluated under in vitro conditions, employing electrochemical polarization techniques and immersion tests for durations of up to 21 days in an artificial urine (AU) solution. The highest hardness value was reached in the Zn-0.5Ag-0.4Al sample with a value of 61.5 HV, and no significant change was observed at higher Al content. The highest and lowest icorr values were measured as 5.71 and 1.09 mu A & sdot;cm-2 in the Zn-0.5Ag and Zn-0.5Ag-0.6Al alloys, respectively. In the bacterial susceptibility study, it was observed that the Al content increased the antibacterial activity, and the highest value was found in the Zn-0.5Ag-0.6Al alloy with 15.25 mm in the interaction with E. coli bacteria. In addition, it was observed that the optimization performed in cell tests with mouse embryonic fibroblasts (MEF), human urinary bladder cancer cells (T24), and prostate epithelial cells (PNT1A) was promising, and the highest potential was observed in the Zn-0.5Ag-0.6Al alloy.
Keywords: Bioabsorbable; Zn-Ag-Al alloy; Urological devices; Degradation; In-vitro corrosion; Cell culture; IN-VITRO DEGRADATION; MECHANICAL-PROPERTIES; MAGNESIUM ALLOYS; AL-MG; ANTIBACTERIAL PROPERTIES; CYTOTOXICITY EVALUATION; SURFACE MODIFICATION; GRAIN-REFINEMENT; URETERAL STENTS; CAST ZINC; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering